The specialty of oral and maxillofacial surgery (OMFS) in Europe – Part 1: service configuration, regulation, and provision - Magennis, Patrick; Hölzle, Frank; Ulrich, Hans-Peter; Acero, Julio; Hutchison, Iain (British journal of oral & maxillofacial surgery, 2022)
Oral and maxillofacial surgical (OMFS) practice and training in Europe is supported by the OMFS Section of the Union of European Medical Specialists (UEMS). Across Europe the number of OMFS specialists per 100,000 varies from 3.0 (Switzerland) to 0.28 (Ireland). The two types of OMFS within the European Union (EU) under Directive 2005/36 and European Free Trade Association (EFTA) treaties are dual degree dental, oral and maxillofacial surgery (DOMFS) and single medical degree maxillofacial surgery (MFS). Automatic recognition of OMFS specialist qualifications is possible only between nations which have the same (or both) types of medical OMFS. Otherwise, individual specialists must apply for a Certificate of Eligibility for Specialist Registration (CESR). DOMFS: 20 European nations have dual degree OMFS. Of these, 12 EU nations are DOMFS in Annex V, 3 are DOMFS in the European Free Trade Association (EFTA) Treaty, and one has mandated dual degree OMFS but is a dental specialty. The United Kingdom has dual degree OMFS. Two MFS nations have had mandated dual degree training for more than 10 years and one has both DOMFS and MFS training, with DOMFS recommended. Although no nation with dual degree DOMFS has transitioned back to single degree MFS, there are pressures to do so within Finland and Norway. MFS: 11 EU nations have single medical degree MFS (and 4 DOMFS nations also have MFS as a legacy specialty). Four nations in the EU/EFTA do not yet have a medical specialty of OMFS: Sweden, Iceland, Denmark, and Estonia.